ANALISIS USER INTERFACE DAN USER EXPERIENCE PADA APLIKASI CAPCUT MENGGUNAKAN METODE USABILITY TESTING - Gibran, M Khalil; Masayu, Kiki; Afda, Mawaddatul; Andini, Reyva Mido; Br Sembiring, Naila Davina (DEVICE : JOURNAL OF INFORMATION SYSTEM, COMPUTER SCIENCE AND INFORMATION TECHNOLOGY, 2026)
In today's digital era, video editing applications are increasingly used, especially by students. One popular application is CapCut. This study aims to analyze the User Interface (UI) and User Experience (UX) of the CapCut application using usability testing methods. The results showed that the UI aspect obtained an average score of 2.94 and the UX aspect obtained an average score of 2.90, categorized as good. Most respondents considered the application's appearance attractive and easy to use, but some users still considered the editing page too busy.